A Republic that is Almost Facing Extinction of Population: Adygea - (:unkn) unknown (MARMARA UNIV, 2018)
The Republic of Adygea is a federal subject of Russia, located in the North Caucasus. It belongs to the Southern Federal District of the Russian Federation, and Maykop is its capital city. The Adygeans (Circassians), who gave their name to the Republic today, live in various regions of the world. The reason of this is the Russo-Circassian war in the 19th century, this is concluded with exile. Within historical background, the demographic characteristics of the region were influenced very much as a result of mentioned catastrophic events. After this date, different ethnic groups were started to be deployed rapidly to the region. While the population of Adygea increased relatively rapidly until the 1990s, the rate of population growth has suddenly slowed down since the disintegration of the USSR, as is the case throughout the Russian Federation. As of 2017, the population structure of the Adyghe Republic has reached a position similar to that of an ordinary Eastern European country, and the rate of population growth slowed down and even came to a halt. It is a known fact that many Turkish citizens in Turkey have Caucasus and especially Adygea origins. Since the academic studies to date are concerned mainly with the North Caucasus and Circassian history, demographic information such as population, population density, urbanization, average life expectancy, median age, crime rates, unemployment data, did not attract the expected attention. However, it is not known exactly how the demographic situations in the motherland where these citizens were exiled structured in the past and today. Therefore, we have addressed and studied Adyghe's population characteristics. All the maps that are used here were prepared in computer environment using GIS and Remote Sensing software. QGIS software was used in mapping.
Keywords: Caucasus; Circassian; Adygea; Demography